Does tooth loss affect dietary intake and nutritional status? A systematic review of longitudinal studies. (December 2017) - Gaewkhiew, Piyada; Sabbah, Wael; Bernabé, Eduardo
Abstract: Introduction/objective: A systematic review was conducted to explore whether tooth loss affects dietary intake and nutritional status among adults. Data: Longitudinal studies of population-based or clinical samples of adults exploring the effect of tooth loss on food/dietary/nutrient intake and/or nutritional status were included for consideration. The risk of bias was assessed using the Newcastle-Ottawa Scale for cohort studies. Sources: A search strategy was designed to find published studies on MEDLINE, EMBASE and LILACS up to March 2017. Study selection: Eight longitudinal studies in 4 countries (United States, Japan, Australia and Brazil) were included. Five of the six studies investigating the association between tooth loss and dietary intake showed significant results. The only consistent association, as reported in 2 studies, was for greater (self-reported) tooth loss and smaller reductions in dietary cholesterol. Three of the 4 studies investigating the association between tooth loss and nutritional status showed significant results. However, most results were contradicting. The quality of the evidence was weak. Conclusion: There is at present no strong evidence on the effect of tooth loss on diet and nutrition, with inconsistent results among the few studies identified. Additional high-quality longitudinal studies should address the limitations of previous studies identified in this review.